Large-Scale Direct Shear Test on Scrap Tire Strip Reinforced Brick Powder - Qiang Ma; Qian Deng; Jia Mou; Shuo Yang; Xu Zhang (Advances in Civil Engineering)
In order to clear the shear mechanism of the scrap tire strips reinforced brick powder, a series of large-scale direct shear tests were carried out on the pure brick powder and reinforced brick powder. The scrap tire strips with 50 mm in length, 5 mm in thickness, and 10 mm, 30 mm, and 50 mm in width were put into the brick powder with volume percentages of 2%, 6%, and 10% as reinforcement, respectively. The results show that the internal friction angle and cohesion increase by adding scrap tire strips into brick powder. The peak shear strength of reinforced brick powder initially decreases, thereafter increases and finally decreases with the increase of volume percentage of the scrap tire strips. And the peak shear strength increases in the initial stage and then decreases with the increase of the scrap tire strips dimension. The optimal dimension and volume percentage of the scrap tire strips are 50 mm × 30 mm × 5 mm and 6%, respectively. In addition, the scrap tire strips provide constraints to restrict the vertical displacement of integral reinforced brick powder, and relative to the pure brick powder, the larger the vertical load is, the greater the decrease of vertical displacement is.